Pelatihan Kader Tutor Sebaya Kerere’ - Kusniyati Utami; Agus Supinganto; Melati Inayati Albayani; Haryani Haryani; Aswati Aswati; Irni Setyawati (Jurnal Pengabdian Pada Masyarakat, 2022)
KERERE' CADRE OF PEER TUTOR TRAINING. Pre-pregnancy health services are carried out since adolescence. Mambalan Village is one of the villages in the Penimbung sub-district which is in the working area of the Penimbung Health Center. Based on information, there were 12 cases of teenage pregnancy during 2019. The results of interviews with village cadres showed that youth posyandu activities had actually been carried out but few attended due to the irregular schedule of youth posyandu activities. The purpose of this service is to form a cadre of peer tutors through cadre training on adolescent reproductive health. Cadre training begins with data collection and problem information, identification of potential youth, coordination with groups of youth posyandu organizers, training, and inauguration. The partner of this service is the village head of Mambalan as the builder of the youth posyandu. The target of the training is as many as 20 teenagers. The results of this service show that adolescents' understanding and knowledge of reproductive health increases after training so that peer tutor cadres are able to provide knowledge to their peers about the dangers of early marriage. It is hoped that the government of Mambalan Village and Penimbung Health Center will increase awareness and awareness of adolescent reproductive health.